"Estudio de factibilidad para la creacion de un centro recreacional agro turistico "mi casita de campo en la finca san Jose-canton El Empalme, año 2012. - Peñafiel Zambrano, María Victoria (2013)
This research was conducted in El Empalme city, to 167 km from the city of Guayaquil, located northeast of the province of Guayas, its limits are: in the west Guayas, on the north Manabí and south by Los Ríos; minimum temperature is 21 ° C, an average annual precipitation 1600-3200 mm and its climate is tropical. The study was executed in 180 days. This work began with the formulation to investigate problematic, which was based on assessing the lack of a recreational center that provides innovative agro tourism options for the user. The proposed objectives for the project were diagnosed by a market study the need for the creation of a recreational center agritourism of the city of El Empalme; Conduct a study of investment and financing to enable the development of implementing this project and determine the feasibility of the project by applying different evaluation techniques that can justify the cost of the project, 2012. In order to comply with the objectives of this work, it was necessary to use the methods: inductive, deductive, and scientific research. The types of research: the field because it made the scene, since literature was based on statistical studies, books and tax provisions, and as applied through interviews, surveys and observations, we aimed to do, to act, builds and modify until the printing of the final work. The survey was conducted by taking a sample of 397 people in a range of ages between 10 and 50 years, in the urban area of the city of El Empalme. Research deepened in the feasibility study and market analysis components, technical and financial, information that became the basis of support for the financial evaluation. The profitability analysis was gotten by the following formulas: Total costs, asset depreciation, accumulated depreciation, cash flow breakeven (PE), Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (R. B / C). To culminate the research could be analyzed in Canton El Empalme, has only conventional recreational options, which we will only offer pools, bar, sports fields, logging into your database 1390 visits a week. The planned establishment of an agro tourism center aims to provide recreational services horseback riding, fishing, open space for family recreation, agro tourist tours of the facilities of the farm, which is expected to meet the 14.5% of the unmet current. The technical study found that the total required investment and operations amounted to ($ 97.40, 28), which will get 60% financing through a commercial credit in the National Development Bank. The economic and financial evaluation, determined that the creation and implementation of agro tourist recreation center results in obtaining various benefits: social is social development achieved the project creates a positive impact as it sees new opportunities for economic development of the canton El Empalme, as well as the possibility of conceiving generated new jobs, and in the negative environmental effect is low because it generates plastic waste and recyclable paper and controllable. Financially the creation of agro tourist recreation center is profitable because it provides an NPV of $ 171,651, an IRR of 48% much higher than the market rate, with a payback period of 2.09 years. Finally we concluded that the hypothesis is fulfilled since the feasibility study determined that if there is profitability in the implementation of agro tourist recreation center "My Shed".